Structured Data Markup dan Format Microdata pada Search Engine Optimization Portal Berita - Teddy Aryono; Seng Hansun (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Revolution of technology makes information demand through internet increases. This has to be followed by implementing Search Engine Optimization (SEO), therefore, sites that contain good information can get top rank in search result by the search engines. This paper describes implementation of structured data markup method to implement an SEO in a website. The objective is to analyze the effectiveness of structured data markup method to increase pageview of a website. Testing is done by building two identical news portal sites and implementing structured data markup on one of those sites. Benchmarking of success is carried out using Google Analytics for 31 consecutive days with the pageview as parameters. The results show that the sites implementing this method has pageviews 5.7% more than the sites that do not implement this method. On the 31st day, guratpena website, that implementing structured data markup, has 871 pageviews, while suaralensa website that does not implement the method only has 822 pageviews.